The Effect of the Current Ratio (CR) and Debt-to-Asset Ratio (DAR) on Return on Assets (ROA) at PT Indocement Tunggal Prakarsa Tbk for the Period 2015–2024 - Refa Liati; Akhmad Akbar (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2026)
This study aims to analyze the effect of liquidity ratios, measured by the Current Ratio (CR), and solvency ratios, measured by the Debt-to-Asset Ratio (DAR), on profitability ratios, specifically Return on Assets (ROA) at PT Indocement Tunggal Prakarsa Tbk, one of Indonesia’s leading cement companies. The background of this study is based on the importance of financial resource management in facing intense business competition, as well as the strategic role of the cement industry in national development. This study is a quantitative descriptive study. The data used are secondary data in the form of PT Indocement Tunggal Prakarsa Tbk’s annual financial reports for the period 2015–2024. The data analysis technique used is multiple linear regression analysis with the aid of the Statistical Package for the Social Sciences (SPSS) program, preceded by classical assumption tests (normality, multicollinearity, and heteroscedasticity). Hypothesis testing was conducted to examine the partial effect of CR on ROA, the partial effect of DAR on ROA, and the simultaneous effect of CR and DAR on ROA.